Feasibility Analysis Of Cut Flower Trading Business In Bogor City - Muhammad Ravy Mulyadi; Yusuf Muhyiddin; I Putu Eka Wijaya (UNIVED Press, Dehasen University Bengkulu, 2023)
Cut flower traders in Bogor City have now begun to decline, therefore it is necessary to conduct a feasibility study to find out whether the cut flower trading business in Bogor City provides decent profits or not to be cultivated. The objectives of this study are; to analyze how much income is obtained from the cut flower business in Bogor City, Analyze the feasibility level of the cut flower business in Bogor City. The sampling technique in this study was to use the purposive sampling method, the samples needed in this study were 26 cut flower traders in Bogor City by combining 13 traders in the fostered zone and 13 cut flower traders in the non-assisted zone of the Bogor City Government. The data analysis used in this study is revenue analysis and R/C Ratio (Revenue Cost Ratio). The results of this study show that the income received in one month by cut flower traders in non-fostered zones and traders in fostered zones can be said to be profitable. The feasibility rate (R/C Ratio) of cut interest efforts in non-fostered zones and fostered zones is equally feasible to strive for.